Is There Any Non-functional Training? A Conceptual Review - Ide, Bernardo N.; Silvatti, Amanda P.; Marocolo, Moacir; Santos, Clarcson P. C.; Silva, Bruno V. C.; Oranchuk, Dustin J.; Mota, Gustavo R. (Frontiers in Sports and Active Living, 2022)
This conceptual review aimed to investigate whether "functional training" (FT) programs are different from traditional strength, power, flexibility, and endurance training programs. A search for the twenty most recent papers published involving FT was performed in the PubMed/Medline database. Definition, concepts, benefits, and the exercises employed in FT programs were analyzed. The main results were: 1) there is no agreement about a universal definition for FT; 2) FT programs aim at developing the same benefits already induced by traditional strength, power, flexibility, and endurance training programs; 3) exercises employed are also the same. The inability to define FT makes differentiation difficult. Physical training programs can be easily described and classified as strength, power, flexibility, endurance, and the specific exercises employed (e.g., traditional resistance training, ballistic exercises, plyometrics and Olympic-style weightlifting, continuous and high-intensity interval training). This proper description and classification may improve communication in sports science and improve interdisciplinary integration. Aiming to avoid confusion and misconceptions, and based on the current evidence, we recommend that the terms FT, high-intensity FT, and functional fitness training no longer describe any physical training program.